Jogos de distância e proximidade: construção do espaço dialógico na arte performativa - Patricia Gomes de Azevedo (2016)
The thesis includes an investigation based on the artistic practice of Patricia Azevedo in collaboration with British artist Clare Charnley. The work is a flexible practice that occurs when the artists are geographically distant or when they are together, taking advantage of these two spatial situations as triggers to develop works and research. On the other hand, this practice is taken as a device for critical reflection about the construction of spaces in performance art, noting in particular the gesture of performing to the camera. Experimenting dialogues betweenthe visual and the verbal, a dynamic action about spaces and gestures takes place, considering artists and works which are reference to the works developed during the period of research here organized in the form of an inventory-book.